Alumni series: the digital health revolution: a pharmacist's guide to embracing emerging technology / Mohd Ghazali Ismail - Ismail, Mohd Ghazali (Faculty of Pharmacy, 2023)
Since 2014, the healthcare industry has witnessed a remarkable transformation with the emergence of digital health technologies. These technologies, ranging from telemedicine and wearable devices to artificial intelligence and blockchain, have revolutionised the way healthcare services are delivered and experienced. As a pharmacist, embracing these emerging technologies is essential to staying ahead in a rapidly evolving landscape. This guide aims to provide pharmacists with a comprehensive overview of the digital health revolution and equip them with the knowledge and skills needed to leverage these technologies effectively. Digital health refers to the use of technology and digital tools to enhance healthcare services, improve patient care, and promote overall wellness. It encompasses a broad range of applications and technologies that leverage digital platforms, devices, software, and data to deliver healthcare services, monitor health conditions, facilitate communication between patients and healthcare providers, and support the management of health-related information.